Pengaruh Citra Perusahaan dan Harga Terhadap Kepuasan Pelanggan di Mediasi Keputusan Pembelian Sebagai Variabel Intervening (Studi Kasus Indihome Bisnis PT. Telkom Witel Medan) - Hermawan, Joko; Tirtayasa, Satria; Suwito, Suwito (Journal of Student Development Informatics Management (JoSDIM), 2023)
This research uses a quantitative descriptive approach with a sample of 100 respondents who are customers of PT Telkom Witel Medan. Data collection techniques in this study used interviews and questionnaires as well as data analysis techniques using Partial Least Square (SmartPls) version 3. The research objective was to identify and analyze the seven conceptual frameworks proposed in the form of the influence of corporate image on customer satisfaction, the influence of corporate image on purchasing decisions, the effect of price on customer satisfaction, the effect of price on purchasing decisions, the effect of purchasing decisions on customer satisfaction, the influence of corporate image on customer satisfaction through purchasing decisions, the effect of prices on customer satisfaction through purchasing decisions. The test results answer the hypotheses of the seven statements in the conceptual framework which are stated as a whole to have a positive and significant effect on this study.